2011
DOI: 10.1590/s0004-282x2011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EuroQol quality of life questionnaire on stroke victims

Abstract: Objective: To validate a quality of life scale, EuroQoL, on stroke patients. Method: 67 patients were scored simultaneously for EuroQoL-5 Dimensions (EQ-5D), NIH Stroke Scale (NIHSS) and modified Barthel Index (mBI). Pearson test was used to correlate each scale. Additionally, 31 patients were examined by two independent evaluators on the same day through application of EQ-5D. Kappa statistics were used to evaluate interobserver agreement. Results: EQ-5D showed good correlation with both stroke severity (NIHSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 25 publications
0
43
0
7
Order By: Relevance
“…Our study builds on previous work 18 that examined the relationships between the EQ-5D, BI, and NIHSS. However, this analysis was conducted in a much smaller sample (n=67) and the correlations observed were weaker than in our study (EQ-5D and NIHSS [r=−0.40]; EQ-5D and modified BI [r=0.51]).…”
Section: Strokementioning
confidence: 95%
“…Our study builds on previous work 18 that examined the relationships between the EQ-5D, BI, and NIHSS. However, this analysis was conducted in a much smaller sample (n=67) and the correlations observed were weaker than in our study (EQ-5D and NIHSS [r=−0.40]; EQ-5D and modified BI [r=0.51]).…”
Section: Strokementioning
confidence: 95%
“…However, they each fail to assess the broad multi-dimensional factors contributing to QoL. Ali et al demonstrated correlation between mRS, BI, and QoL (generic and disease specific); self-reported QoL had a significantly stronger association with mRS while proxy QoL had stronger association with BI 2021,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Each surviving case also is contacted for 3-, 6- and 12-month follow-ups, which include evaluation of modified Rankin scale, 11 Barthel Index, 12 medication use, EuroQol EQ-5D, 13 and Health State Scale. 14 …”
Section: Methods and Research Designmentioning
confidence: 99%